2000
DOI: 10.1034/j.1398-9995.2000.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in the desert: spectrum of the sensitizing aeroallergens

Abstract: These results show that even in a desert environment, pollens and house-dust allergens may be important sensitizing allergens. They also illustrate how practices that "green" the desert can affect public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
53
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 21 publications
12
53
1
1
Order By: Relevance
“…Differences in the rate of positive SPT can be due to various factors such as number of allergens tested, climatic region and age of patients. With regard to optimum growing conditions, including high humidity for molds (28,29), Unexpectedly, this particular allergy was also found in hot and dry regions, like Saudi Arabia (6) and Kuwait (9,30), It might be associated with increasing the use of air conditioners inside the houses which make good environment for molds to grow and increase exposure to their allergens (26,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the rate of positive SPT can be due to various factors such as number of allergens tested, climatic region and age of patients. With regard to optimum growing conditions, including high humidity for molds (28,29), Unexpectedly, this particular allergy was also found in hot and dry regions, like Saudi Arabia (6) and Kuwait (9,30), It might be associated with increasing the use of air conditioners inside the houses which make good environment for molds to grow and increase exposure to their allergens (26,28).…”
Section: Discussionmentioning
confidence: 99%
“…Molds are ubiquitous in our environment and are common allergens in allergic diseases. Mold spores can be found in outdoor or indoor environments, but exposure can also occur by having contact with saprophytic species or by ingestion of edible mushrooms (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [96] reported the effect of sandstorms on allergic rhinitis in residents of Taipei, Taiwan, revealing that subjects exposed to sandstorms developed allergic rhinitis with a prevalence that was prominent in 19% of cases. Some of the rhinitis-and asthma-causing allergens, for example plant and grass pollens, fungal spores, molds, dust mites, anthropogenic emissions, and organic detritus, are also found in desert dusts [97][98][99].…”
Section: Desert Dust Associated With Asthma and Rhinitismentioning
confidence: 99%
“…Several studies (Charpin et al, 1988;Ezeamuzie et al, 2000) examined the link between asthmatics and allergens in environments with dry (RH< 40%) conditions. Ezeamuzie et al Three studies (Infante-Rivard, 1993;Smedje et al, 1997a;Kovesi et al, 2007) focused on understanding the effects of environmental conditions on young asthmatics and children with a history of lower respiratory tract infections (LRTIs).…”
Section: Asthma and Respiratory Infectionsmentioning
confidence: 99%
“…Table 3 details the ages of human subjects in health, comfort, and IEQ tests. A few studies considered children under the age of 18, using surveys or environmental sampling in the homes of children with asthma (Infante-Rivard, 1993;Ezeamuzie et al, 2000;Kovesi et al, 2007) and dust mite allergies (Munir et al, 1995). Smedje et al, 1997a surveyed Swedish teenagers (13-14 years old) and took measurements in public school classrooms.…”
Section: Knowledge Gapsmentioning
confidence: 99%